Mantenimiento de motores en la enseñanza de los estudiantes de la carrera de Mecánica Automotriz - Urgiles Ortiz, Freddy Omar (2021)
This project aims to contribute to the solution of the main problems that arise in the automotive field, directing us to a correct and adequate preventive maintenance of vehicles with gasoline engines, determining the incidence in the teaching of students of the mechanics career automotive, thus achieving great results, efficient and effective maintenance and in this way the owners of the vehicles can carry out their activities satisfactorily and without setbacks. It is necessary to take into account that internal combustion engines through a series of elements, systems and mechanisms work together resulting in the effective operation of the engine, so it is necessary to identify the operation of each of them and also a constant observation of its operation. Individual operation of each of the engine systems, elements and mechanisms. The auditory part plays a very important role in being able to detect the operation of each one of them since hearing strange noises indicates an alert signal that one of the elements, systems or mechanisms needs immediate control in order to avoid setbacks or expenses That occurs. Demand a lot of money. It is important that the student detect anomalies or malfunctions of the engine and also the useful life of the different components.